2017
DOI: 10.1044/persp2.sig11.42
|View full text |Cite
|
Sign up to set email alerts
|

Leading the Way With Supervision Training: Embracing Change and Transforming Clinical Practice

Abstract: The practice area of clinical supervision has recently acknowledged a demand for efficacious and accessible supervision training opportunities. As with any area of clinical practice, effective supervision requires prior training. Those who engage in supervision practices must be well-trained to adequately support the advancement of evidence-based clinicians. This article will discuss the upcoming changes in supervision training requirements and how embracing these changes will ultimately transform the fields o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Some evidence has suggested that this style of teaching may create a hostile teaching-learning environment that reduces confidence and motivation and promotes fear of learning (Oh, 2005;Tofade et al, 2013). including speech-language pathology and audiology, have recognized the significance of formalized clinical education training (American Occupational Therapy Association, n.d.; American Physical Therapy Association, n.d.; ASHA, 2016;Kilminster, Cottrell, Grant, & Jolly, 2007;Procaccini, McNamara, & Lenzen, 2017). The field of medicine has long established that formal clinical teaching training improves learning outcomes (Bazuin & Yonke, 1978;Greenberg, Goldberg, & Jewett, 1984;Neher et al, 1992).…”
Section: Setting a Positive Environmentmentioning
confidence: 99%
“…Some evidence has suggested that this style of teaching may create a hostile teaching-learning environment that reduces confidence and motivation and promotes fear of learning (Oh, 2005;Tofade et al, 2013). including speech-language pathology and audiology, have recognized the significance of formalized clinical education training (American Occupational Therapy Association, n.d.; American Physical Therapy Association, n.d.; ASHA, 2016;Kilminster, Cottrell, Grant, & Jolly, 2007;Procaccini, McNamara, & Lenzen, 2017). The field of medicine has long established that formal clinical teaching training improves learning outcomes (Bazuin & Yonke, 1978;Greenberg, Goldberg, & Jewett, 1984;Neher et al, 1992).…”
Section: Setting a Positive Environmentmentioning
confidence: 99%